ANALISA KUALITAS PELAYANAN UNTUK MENINGKATKAN KEPUASAN PELANGGAN MENGGUNAKAN DIMENSI SERVQUAL DAN MODEL KANO (STUDI KASUS PT TELKOM,PRODUK SPEEDY DI SEMARANG) - Sindhu Pradipta; Hery Suliantoro; Rani Rumita (Industrial Engineering Online Journal, 2012)
PT Telkom Speedy who kind of Speedy product is Telecommunications Company who engaged in Internet service that uses only one cable line in Indonesia, which means it must be able to meet all the needs of customers. It can be said that the ministry is a direct or indirect interaction in which customers can provide an assessment of the quality of products and services offered by Speedy. Speedy received various suggestions from customers about the lack of quality of services provided, which can degrade the image of Speedy in the eyes of society because of the expected service is not met. Should it be triggered by Speedy products to evaluate the quality of service, and make improvements in order to achieve customer satisfaction. One dimension to analyze the quality of service is the Service Quality. This approach is an indicator to determine the quality of service. In addition the method used in this study is Kano. This method has the purpose of categorizing the attributes of products and services based on how well the product / service is able to satisfy customer needs. This model is used in activities such as identifying customer needs, determining the functional needs, concept development and analysis of competitive products. Based on the analysis of the Kano model to categorize its attributes obtained after nine variables that more priority is entered in the category of Attractive and does not exclude the category of One-dimensional, because this category deserve to be upgraded as well, although the preferred attractive category. Then for the category of Must-be sufficiently preserved because it is the basis of a necessity of the companies have these attributes. The above can be said that quality is not good so that speedy service at the proposed improvements to service quality is to deepen understanding of what speedy employees become customer requirements with training conducted by the Speedy